Seroprevalence of enzootic bovine leukosis (EBL): a systematic review and meta-analysis (Research, Society and Development, 2020)
Enzootic bovine leukosis (EBL) is a viral disease with negative impact on the economy, and the virus has been linked to breast cancer in women and its DNA detected in fresh milk and raw beef for human consumption. In this context, epidemiological surveys allow the knowledge of epidemiological indicators of infection, guiding control programs and consequently making it possible to control and/or eliminate the virus in cattle populations. Therefore, the objective of the present study was to carry out a systematic review with meta-analysis on EBL seroprevalence. Complete articles and brief communications from indexed journals that contained data on the seroprevalence of EBL and described the diagnostic methods used to identify the infection were selected. The study followed the recommendations of the PRISMA methodology - Preferred Reporting Items for Systematic Reviews and Me[1]ta-Analyzes. In turn, from a total of 581 studies 15 met the eligibility criteria, and the meta-analysis showed a combined prevalence of 31% (95% CI = 25 – 37%), although with high heterogeneity among the studies, which was attributed to research designs, years of publication of the studies, quantity and age of the animals sampled, exclusive use of dairy herds and heterogeneity among countries. Therefore, this scenario suggests the need for standardization of researches related to epidemiological studies for EBL, specifically cross-sectional surveys, with the use of planned sampling, adjustment of rates according to parameters that may influence the prevalence and specific analyzes that provide the determination of reliable epidemiological indicators.